Estimating discard survival of European sea bass (Dicentrarchus labrax) in the UK commercial hook‐and‐line fishery. (28th October 2021) - Lamb, Philip D; Randall, Peter; Weltersbach, Marc Simon; Andrews, Barnaby; Hyder, Kieran
Abstract: Despite the implementation of technical management measures to facilitate stock recovery of European sea bass, Dicentrarchus labrax (L.), the survival rate of discarded hook‐and‐line caught sea bass remains unknown. This makes the effectiveness of management measures that result in discarding difficult to assess. Therefore, a questionnaire was distributed to 421 UK‐based commercial hook‐and‐line fishers (65 respondents) to characterise how sea bass are caught, handled and released. Responses suggested fishing was selective with a reported estimated mean discard rate of 12.9% (±3.3% SE). Low rates of foul and deep hooking, and short periods of air exposure were reported. Combined with data from a post‐release mortality experiment using hook‐and‐line caught captive sea bass, a fleet‐wide discard survival rate of 89.3% (±2.6% SE) was calculated for the UK commercial hook‐and‐line sea bass fishery. This survival rate suggests that technical management measures, for example minimum conservation reference sizes and catch limits, could be effective tools for managing the sea bass hook‐and‐line fishery.